Prospectus 1995/96 : School of Applied Sciences / Institut Teknologi MARA - Institut Teknologi MARA, ITM (Institut Teknologi MARA, ITM, 1995)
School Of Applied Sciences At Institut Teknologi MARA, Background, Academic Programme, Academic Staff, Students, Facilities Available, Quality Assurance : System Of Academic Advisers, System Of Tutor-Tutee, Admission Requirement, System Of Evaluation, Academic Requirement, Coding System Of Subjects, Description Of Common Subjects, Curricula And Course Descriptions and Glossary Of Academic Terminology.